2013
DOI: 10.1021/bi400779r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bleomycin-Mediated Cleavage of a Hairpin DNA Library

Abstract: A study of BLM A5 was conducted using a previously isolated library of hairpin DNAs found to bind strongly to metal free BLM. The ability of Fe(II)•BLM to effect cleavage on both the 3' and 5'-arms of the hairpin DNAs was characterized. The strongly bound DNAs were found to be efficient substrates for Fe•BLM A5-mediated hairpin DNA cleavage. Surprisingly, the most prevalent site of BLM-mediated cleavage was found to be the 5′-AT-3′ dinucleotide sequence. This dinucleotide sequence, and other sequences generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Bleomycin preferentially cleaves DNA at particular dinucleotide sequences. DNA sequence specificity studies with purified plasmid sequences have indicated that the dinucleotides 5′-GT* and 5′-GC* are preferentially cleaved by bleomycin [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. For ease of discussion in this review, the bleomycin cleavage site nucleotides are numbered with respect to the cleavage site at nucleotide position 0, and the positions discussed are from −3 to +2 (see Table 1 ).…”
Section: Bleomycin Cleavage Specificity With Purified Dnamentioning
confidence: 99%
“…Bleomycin preferentially cleaves DNA at particular dinucleotide sequences. DNA sequence specificity studies with purified plasmid sequences have indicated that the dinucleotides 5′-GT* and 5′-GC* are preferentially cleaved by bleomycin [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. For ease of discussion in this review, the bleomycin cleavage site nucleotides are numbered with respect to the cleavage site at nucleotide position 0, and the positions discussed are from −3 to +2 (see Table 1 ).…”
Section: Bleomycin Cleavage Specificity With Purified Dnamentioning
confidence: 99%
“…Previous studies have focused on the two known DNA cleavage sites that BLMs are known to interact with, mainly 5’-GC-3’ and 5’-GT-3’[24], however a preference of cleavage site is not well understood [19,25]. The interactions of different MBLMs with DNA including Fe(II)- [2628], Zn(II)- [17,18], Co(III)- [6,2023,2934], and Cu(I)-bound BLMs [35], have been examined. However the possibility of different coordination geometries of these metal centers to BLM and their repercussions on the final structure of the MBLM-DNA triad have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer mechanisms of each of these molecules are however different from each other. While actinomycin D triggers p53-independent apoptosis in cells [21] and bleomycin exhibit oxygen and metal ion-dependent cleavage of the DNA [22]. Doxorubicin, in turn, inhibits DNA and RNA replication and transcription and causes oxidative stress in tumor cells, triggering membrane, protein and DNA damage [23].…”
Section: Discussionmentioning
confidence: 99%